Opening Eyes onto Inclusion and Diversity - Carter, Susan; Abawi, Lindy; Lawrence, Jill (Open textbook library., 2019)
Susan Carter; Professor Lindy-Anne Abawi; Professor Jill Lawrence; Associate Professor Charlotte Brownlow; Renee Desmarchelier; Melissa Fanshawe; Kathryn Gilbey; Michelle Turner; and Jillian Guy